Projectile Horizontal and Vertical Motion Independence Demonstrator - Rey-Mark Basagre; Juan Miguel Alpaño; Joven Barquilla; Joy Bongalos; August Christopher De La Torre; John Carlo Nares (SEAQIS Journal of Science Education, 2022)
This paper developed an instructional tool called Projectile Horizontal and Vertical Component of Motion Independence Demonstrator, user manual, and learning module to physically demonstrate the projectile motions’ abstract concept. Specifically, it was pursued to develop an instructional tool, user manual, and learning modules on projectile motion, determine its evaluation results from the experts, and determine recommendations drawn from the evaluators for the improvement, utilization, and dissemination of developed instructional tools and learning modules. Quantitative and qualitative data were gathered using a four-rating Likert scale evaluation sheet. Results showed that instructional tool and user manual are "very satisfactory" and suggestions for improvement, utilization, and dissemination of the instructional materials are forwarded. Further, it is recommended for replication and use in secondary school as instructional material.